2015
DOI: 10.1111/liv.12921
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin vs. lactulose in treatment of minimal hepatic encephalopathy

Abstract: Non-inferiority of rifaximin over lactulose for MHE reversal was not established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…Lactulose showed significant reduction in serum, liver and brain ammonia levels. The present results are consistent with the previous study reporting that lactulose could significantly lower the level of hyperammonemia [16].…”
Section: Discussionsupporting
confidence: 94%
“…Lactulose showed significant reduction in serum, liver and brain ammonia levels. The present results are consistent with the previous study reporting that lactulose could significantly lower the level of hyperammonemia [16].…”
Section: Discussionsupporting
confidence: 94%
“…It was shown in an open-label study that lactulose can prevent development of the first episode of overt HE but the study needs to be replicated in a larger study in a blinded fashion before firm recommendations can be made [108]. Studies using lactulose and rifaximin have shown improvement in quality of life [109,110] and also in driving simulator performance [111,112]. Probiotics have also been used but the open-label nature, varying amounts and types of organisms and different outcomes make them difficult to recommend as therapeutic options at this time [113–115].…”
Section: Treatmentmentioning
confidence: 99%
“…All agents shown to be effective for overt HE have also been shown to be effective for covert HE, with the addition of carnitine and acylcarnitine …”
Section: Covert Hepatic Encephalopathymentioning
confidence: 99%
“…All agents shown to be effective for overt HE have also been shown to be effective for covert HE, 67,71,72 with the addition of carnitine and acylcarnitine. 73,74 A low-cost and ecological strategy is summarised in Figure 2.…”
Section: Covert Hepati C En Cephalopathymentioning
confidence: 99%